WASTE MANAGEMENT STRATEGIC PLANNING (WASTE MANAGEMENT IN JAYAPURA CITY) - Lazarus B. Ramandey (Diponegoro University, 2016)
Abstract: This study deals with urban waste management in general by considering key issues in waste management in Indonesia and various problem solving alternatives dealing with waste problem referring to waste management in developed countries (Curitiba). In addition, problems faced will be discussed with the systems approach including: institutional sub-system (sub-system of institutions), operational technique sub-system (sub-systems engineering), financial sub-system, legal and regulatory sub-system (law sub-system) as well as public and private role sub-system. Population growth that is accompanied by high urbanization has resulted in increasingly high volume of waste that must be managed every day. It is increasingly difficult for management and waste management are less than optimal. Similarly, the active role and public awareness as well as the financing are still very low. The system approach can assist in solving the complexity of the problem of waste management by looking at the issues comprehensively. Keywords: urban waste management, population growth, public awareness